Liquid-liquid extraction of zirconium(IV) from sulphuric acid medium using a binary mixture of tri-n-octylamine and Cyanex923 in kerosene - Sahoo, Amit; Swain, Jaykishon; Bhatta, Bhikari Charana (European Journal of Chemistry, 2022)
The extraction behaviour of zirconium(IV) from sulfuric acid medium has been studied with a binary mixture of tri-n-octyl amine (TOA) and Cyanex923 (a mixture of four trialkyl phosphine oxides) in kerosene using a novel liquid-liquid extraction method. Quantitative extraction of zirconium(IV) with binary mixture of Cyanex923 and TOA in kerosene was studied by changing different parameters such as acid variation, extractant variation, effect of chloride ion concentration, effect of temperature, metal concentration variation, diluent effect, and pH effect. The percentage of extraction of zirconium(IV) decreased when the concentration of Cyanex923 and TOA increased. The percentage of zirconium(IV) was observed as 97.56% in a binary mixture of 0.007 M Cyanex923 and 0.06 M TOA. Kerosene was found to be an effective diluent for the extraction of zirconium(IV) with 97.56% extraction using a binary mixture of Cyanex923 and TOA. In addition, the stripping of the zirconium(IV) metal ion in the organic phase was also examined.